Building Institutions for the Next 50 Years of Creativity Research. (12th December 2017) - Silvia, Paul J.
Abstract: The Journal of Creative Behavior 's remarkable half‐century is a good occasion for reflecting on the role of a scholarly field's institutions in fostering creative work. In creativity studies, some of our institutions are flourishing, particularly our many excellent peer‐reviewed journals. But we face some institutional challenges that will require some creative solutions from creativity researchers. This article considers three challenges: (a) how to train and place the next generation of scholars when so few creativity researchers work at doctoral‐level graduate programs; (b) how to tighten the field's social network by bringing together people from different subfields and career stages in face‐to‐face gatherings; and (c) how to identify and develop the leadership needed to manage our scholarly organizations.